Critical Administrative Constraints to Service Delivery : Improving Public Services in Afghanistan's Transformational Decade - World Bank (Washington, DC, 2014)
Since 2001, the Afghan population's access to basic services has greatly improved in nearly all sectors. School enrolment has increased sharply, with over eight million children currently enrolled in school, of which 39 percent are girls. Current strategies for improving sub-national service delivery focus on delegating greater authority to provincial and district administrations. This report aims to identify administrative constraints in three key sectors of public service delivery, education, health and agricultural extension services. The analysis follows the service delivery chain, from central to provincial, through district to community level, and is particularly concerned to examine service delivery in these three sectors through the window of sub-national governance and its relations to the service delivery mandates of line ministries. The study provides the Government of Afghanistan with recommendations on how to alleviate critical constraints to service delivery at sub-national levels on a sustainable basis, in the context of an expected restrained fiscal future. The report's main findings are based on qualitative research. The key findings are based on existing literature and reports as well as field visits to 5 provinces and 10 districts and qualitative analyses of over 171 key-informant interviews on different levels of service delivery administration, 68 in-depth interviews with community leaders, and a community household survey in 20 communities spread over 5 provinces and 55 service facilities (for example, schools and clinics) were assessed. The report is split into six sections: section one gives executive summary; section two provides a brief introduction to the study objectives and clarifies some key definitions; section three outlines the methods used to perform the analysis; sections four, five, and six provide in-depth discussions of education, health, and agriculture extension respectively; and section seven provides recommendations and concludes. The over-arching governance structures and further methodological details are given in appendix one. All references and research tools are presented in annexes.